2014
DOI: 10.12669/pjms.311.6544
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary manifestations of systemic lupus erythematosus patients with and without antiphospholipid syndrome

Abstract: Objective:To uncover the pulmonary manifestations of Systemic Lupus Erythematosus (SLE) patients alone and to compare findings with antiphospholipid syndrome (APS) associated with SLE.Methods:This cross sectional comparative study was carried out at King Khalid University Hospital (KKUH)/King Saud University (KSU), a tertiary care hospital, Riyadh, Kingdom of Saudi Arabia. From June 2012 to March 2014, 96 diagnosed SLE patients with respiratory symptoms were included in the study and divided into two groups. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…24 Also, in this study, longer disease duration and higher frequency of venous thrombosis (DVT and pulmonary embolism) was found in group 1 than in group 2. This observation agrees with the findings of Hamadani and colleagues, 2015, 25 who reported that DVT was present in 3% of SLE patients compared to 27.6% of SLE/APS patients, pulmonary embolism was 3% in SLE patients compared to 34.5% in SLE/APS patients, and abortion was 7.5% of SLE patients compared to 27.6% of SLE/APS patients and they correlated the increased duration of the disease to higher frequency of complications.…”
Section: Discussionsupporting
confidence: 92%
“…24 Also, in this study, longer disease duration and higher frequency of venous thrombosis (DVT and pulmonary embolism) was found in group 1 than in group 2. This observation agrees with the findings of Hamadani and colleagues, 2015, 25 who reported that DVT was present in 3% of SLE patients compared to 27.6% of SLE/APS patients, pulmonary embolism was 3% in SLE patients compared to 34.5% in SLE/APS patients, and abortion was 7.5% of SLE patients compared to 27.6% of SLE/APS patients and they correlated the increased duration of the disease to higher frequency of complications.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the other comorbidities, in our study it was determined that the presence of antiphospholipid syndrome predisposes to the presence of ARI. In similar studies, this association has been established, especially with the presence of pulmonary thromboembolism . One important finding of the present study is the presence of pericardial disease as a marker of ARI, since a statistically significant association was found in both the bivariate and multivariate analyses, which has not been reported in other studies until now, thus identifying a risk factor of significant value in patients with SLE.…”
Section: Discussionsupporting
confidence: 74%
“…The prevalence of PH in SLE was 2.8–23.3% 9. A comparative study was conducted in which various pulmonary manifestations in SLE patients have been studied and pulmonary hypertension was found to be one of the important complication in such patients 12. In another meta-analysis of various studies, it was found that PAH was found in 8% of SLE patients 13.…”
Section: Discussionmentioning
confidence: 99%